Variations in individual player area in youth football matches: the effects of changes of players' age, numerical relations, and pitch zones. (2nd January 2022) - Coito, Nuno; Folgado, Hugo; Romero, Félix; Loureiro, Nuno; Travassos, Bruno
ABSTRACT: The aim of the study was to quantify the individual player area (IPA) that emerges during football matches at youth levels, considering different numerical relations and pitch zones. Two hundred and twenty-eight players, divided by U15, U17 and U19, participated in the study. Jonckheete-Terpstra and Kruskal Wallis nonparametric tests were used to compare the IPA according to variations in players' age, numerical relations and pitch zones considered for analysis. All ages and numerical relation results revealed the highest IPA in the zones closer to the goal and were lower in the middle of the pitch. For 3 × 3 to 10 × 10 numerical relations, the IPA was higher in the U15 and lower in the U17. The greater differences between the age groups concerned numerical relations of 6 × 6 to 10 × 10 (p ≤ 0.001). The effect size was moderate between the U15 and U17 in numerical relations of 8 × 8 to 10 × 10. Results suggest that the manipulation of IPA during training sessions should respect players' age and be adjusted considering the numerical relation and the tactical purpose of coaches.